Strong macrobenthic community differentiation among sub-Arctic deep fjords on small spatial scales - Kokarev, Valentin; Tachon, Mathieu; Austad, Marthe; McGovern, Maeve; Reiss, Henning (Estuarine, Coastal and Shelf Science, 2021)
publishedVersion